Episódios de depleção de sódio aumentam a ingestão espontânea de açúcar - Santos, Bruna Maitan (2015)
Motivated behaviors may share common reward mechanisms and crosssensitization. The objective of the present study was to find out if history of sodium depletion, which sensitises sodium appetite, also sensitizes sugar intake rat. Sodium appetite was induced by two treatments that raise the production of angiotensin II, diuretic furosemide combined with 24 hours of removal of ambient sodium or furosemide combined with low dose of angiotensin converting enzyme inhibitor captopril (Furo/Cap); and it was blocked by NMDA antagonist (MK-801). Each treatment was repeated three to fours times with an interval of 4 or 7 days between two repetitions. About 7 days after the last repetition, sucrose-naïve animals entered a first 2-h sucrose test under hydrated and fed (need-free) condition. The sucrose test was repeated once a day for a total of five consecutive days. Animals with history of either treatment that produced sodium depletion ingested more 10% sucrose in the sucrose test than control animals, which were never sodium depleted. The effect was stronger in the first tests for sucrose, after that groups ingested similar amounts of sucrose after the second sucrose test. Repeated intracellular dehydration (gavage of 2 M NaCl), instead of sodium depletion, was ineffective to alter the later sucrose intake test. Systemic administration of MK-801, an N-methyl-D-aspartate (NMDA) receptor antagonist, combined with Furo/Cap prevented the enhancement observed in 10% sucrose intake. The results suggest that 1) history of dehydration, particularly that involving production of angiotensin II, sensitizes sugar consumption in sucrosenaïve animals, 2) sensitization of sugar consumption depends on plastic events mediated by NMDA receptors.